Penapisan Isolat Rizobakteri dari Perakaran Tanaman Kedelai yang Sehat untuk Pengendalian Penyakit Pustul Bakteri (Xanthomonas axonopodis pv. glycines) - Yulmira Yanti; Trimurti Habazar; Zurai Resti; Dewi Suhalita (Universitas Lampung, 2013)
Screening of indigenous rhizobacteria from healthy soybean root to control bacterial pustule (Xanthomonas axonopodis pv. glycines) using in planta technique. Plant growth promoting rhizobacteria are a group of bacteria that actively colonize plant roots, increase plant growth and control plant pathogens. The aim of this study was to obtain rhizobacteri isolates which have the ability to control bacterial pustule and increase growth and yield of soybean. This method based on in planta selection of enhanced competitive soil root-colonizing bacteria from soil samples of healthy soybean root at endemic area of bacterial pustule in Darmasraya District and Sijunjung District, West Sumatera. We characterized only the best rhizobacteri isolates which have ability to control bacterial pustule and to increase growth and yield of soybean. This type of characterization has possibility to find new, easy and cheap biocontrol organisms. Ten Rhizobacteri isolates were introduced via seed treatment (108 cfu/ml) and soil drench to 3 week old soybean seedling. Xanthomonas axonopodis pv. glycines were inoculated to one month old of soybean seedling. The effect of rhizobacteria on disease incidence, disease severity, plant growth and yield of soybean were evaluated. We have found that two selected rhizobacteri isolates from soybean (P12Rz2.1 and P14Rz1.1) were the best isolates in promoting growth and the of the soybean plants with the effectiveness 20.62 % and 20.47 %.